Vehicle Security System Using Sms (Short Message Service) As Monitoring In Motorcycle Vehicles: Vehicle Security System Using Sms (Short Message Service) As Monitoring In Motorcycle Vehicles - Astuti, Nuraeni Puji; Ritzkal, Ritzkal; Hendrawan, A Hendri (Institute of Computer Science (IOCS), 2020)
Private vehicles are valuable assets for everyone. Each vehicle owner usually has their own way of protecting their vehicle from damage or loss, with many cases of motor vehicle theft in Indonesia making vehicle owners to be vigilant. Moreover, the lost vehicle will be difficult to find, one reason is the difficulty to track the whereabouts of the vehicle during the theft. Various efforts of vehicle owners to improve the safety of motorized vehicles that are parked, both in the public parking area or on the yard of the house, so that it is not easy to trigger theft. ) Producing a system that can monitor and request the location of a motorcycle vehicle when the vehicle is in danger or is stolen. The research method used is an analysis consisting of analysis of work methods and requirements analysis, a design consisting of hardware design and software design, an application consisting of hardware application and software application and finally a test consisting of testing of GPS , testing of GSM, testing all components and testing SMS applications. the conclusion of this research is (i) The hardware manufacture of